A needs assessment for an intervention on supporting breastfeeding at work in a Cape Town clothing factory - Heyns, Hilde (Organisational Psychology, 2022)
The University of Cape Town (UCT), in collaboration with the South African Medical Research Council (SAMRC) and Middlesex University, London, has been requested by the SACTWU Worker Health Programme to design, implement and evaluate an intervention on workplace breastfeeding support for the clothing and textile industry. This study will form part of the bigger project and the results will be utilised in the planning and designing of an intervention on workplace breastfeeding support. Returning to formal employment has been identified as one of the leading barriers to exclusive and continued breastfeeding, especially among women working in low-income jobs. Women working in low-income, low skilled jobs are often easily replaceable and have little bargaining power to request their breastfeeding rights. South Africa's clothing industry employs mostly black women, who hold low-income positions. Clothing factories tend to have rigid working conditions, which could make it difficult for mothers to continue with breastfeeding once they return to work. Few studies have been conducted of breastfeeding support in the workplace in South Africa and no studies were found of breastfeeding support in clothing factories in South Africa. There is a need for more studies to be conducted in workplaces in South Africa, especially in the clothing industry. International studies have found that workplace breastfeeding support interventions can contribute to increased breastfeeding prevalence rates in factories. To increase the rates of breastfeeding in clothing factories, a workplace breastfeeding support programme would need to be developed and implemented. Before designing an intervention, it is important to first conduct a needs assessment to determine whether there is a need for an intervention on workplace support for breastfeeding in the clothing and textile industry. The purpose of the needs assessment in this study was to determine whether there was a need for an intervention on workplace support for breastfeeding in the clothing and textile industry, and if so, what the nature and extent of the need was and the programme activities that were most suitable to address the need. A convergent parallel research design was adopted, which is also known as a mixed methods approach. Quantitative data was collected through a semi-structured survey that was administered to the employees at the factory. In addition, qualitative data was collected through interviews conducted with employees (mothers) and supervisors at the factory. There were various barriers in the factory that made it difficult for women to express breast milk at work, including a lack of time to express, a lack of proper breastfeeding facilities, a lack of information about mothers' breastfeeding and a lack of support from factory management, supervisors and co-workers. There was also a lack of awareness of the law regarding breastfeeding and there was no breastfeeding policy in place. The study found that there was a need for increased support to breastfeeding mothers in the factory, including the support from factory management, supervisors and co-workers, the provision of adequate breastfeeding facilities and breaks and the provision of information about mothers' breastfeeding to all employees. It is also important to develop a breastfeeding policy in the factory which provides clear guidelines on how to support breastfeeding women. According to the findings of the needs assessment, there is a need to design and implement an intervention on workplace support for breastfeeding, to enable women working in a clothing factory to continue breastfeeding when they return to work. The last chapter will include recommendations for the SACTWU Worker Health Programme to design and implement an intervention on workplace breastfeeding support for the clothing and textile industry. Although this study focused only on a single large factory, the basic principles can still be applied and adapted to other clothing factories.